Sistem Reputasi Penjual dalam Proses Pengambilan Keputusan Pembelian di Platform C2C E-commerce - Agustina, Lidya; Kurniawan, Firman (UI Scholars Hub, 2018)
This study discusses the process of purchase decision making which made through online transaction in customer to customer (C2C) e-commerce platform. Online review and online rating have been known as a part of electronic word of mouth which has an impact on buyer's purchase decisions. This study use Kotler and Keller's (2009) purchase making decision process to finds out the purchase decision making process which happens through C2C e-commerce. This study also aims to finds out how online reviews and online rating are used in purchase decision making process. This study uses post-positivistik paradigm with qualitative approach and case study strategy. Data were obtained from in-depth interview and literature studies. The results of this study show that the informations in online review and online rating can provide an overview of seller's reputation and form buyer's perception of products and services quality. The results also indicate that in the purchase making decisions process, there is a zero moment of truth phase. In this phase, buyers learn about the product or seller's reputation through the information that they got from online sources. One of the informations used in zero moment of truth is from online review and online rating.